Making history: Sources of organizational history and its rhetorical construction. Issue 4 (December 2015) - Oertel, Simon; Thommes, Kirsten
Highlights: History can be a source of competitive advantages of a firm. There exist micro- and field-level reservoirs of firm history. There are three types of history utilization: exploitation, denial, and appropriation. History can be constructed by managers and other stakeholders. Abstract: The study proposes a framework for a better understanding of an organization's sources of history as well as how history is rhetorically constructed in order to generate sustained competitive advantages. The empirical setting is the East German watchmaking industry after the reunification of Germany in 1990. Our framework distinguishes between micro- and field-level sources of firm history as well as three types of history application by firms—i.e., history exploitation, history denial, and history appropriation. Based on archival data, homepage contents of the firms, and interviews with managers, results of our comparative case study offer insights on how and why firms (a) exploit or deny history; (b) appropriate history; and (c) make appropriated histories trustworthy. Discussing our findings, we contribute to a more comprehensive understanding of how organizations utilize history to develop competitive advantages.